FRI0169 Influence of anti-tnf therapy on the risk of myocardial infarction in subjects with rheumatoid arthritis: results from the bsrbr-ra. (23rd January 2014) - Low, A.; Lunt, M.; Mercer, L.; Bruce, E.; Consortium, B. C. C.; Dixon, W.; Hyrich, K.; Symmons, D.
Abstract : Background: Subjects with RA are at increased risk of premature cardiovascular disease (CVD) including myocardial infarction (MI), partly through shared inflammatory mechanisms. Anti-TNF therapy may influence this risk through control of inflammation and mediation of other CV risk factors. Objectives: The aim of the analysis was to study the association of anti-TNF therapy with the risk of MI in routine UK clinical practice. Methods: The BSRBR-RA is an ongoing national prospective observational cohort study. Subjects with RA starting anti-TNF (etanercept, infliximab, adalimumab) and a biologic-naïve comparator cohort of subjects exposed to nbDMARD were recruited 2001-2009. All were followed by clinician & patient questionnaires 6-monthly for 3 years, annual clinician questionnaires thereafter and linked to the national death register. All reported MIs from any source were validated against the 2007 AHA/ESC MI criteria. Additional criteria were acute thrombolysis/angioplasty for MI or MI as the underlying cause of death on death certificates. Subjects were censored at 20/4/2010, death, incident MI or date of last clinician follow-up, whichever came first. Subjects with prior CVD were excluded from analysis. Risk of MI was compared between nbDMARD and subjects ever exposed to anti-TNF therapy using Cox regression adjusted by propensity score deciles (PD; Table). The PD included age, gender, RA-related factors, CV risk factors & drugs. Risk of MI was explored further with different drug exposure models and also modelled over time. 30-day and 1-year all-cause mortality post-MI was compared between nbDMARD and anti-TNF subjects using multivariate logistic regression, adjusted for the same confounders. Results: 235 verified incident MIs were analysed; nbDMARD: 43 in 10337 person-years (pyrs), anti-TNF: 192 in 55636 pyrs (42 v 35 per 10, 000 pyrs; Table). There was a trend for a reduced risk of MI in subjects ever exposed to anti-TNF compared to nbDMARD: PD-adjusted hazard ratio 0.65 (0.42-1.01). Risk estimates were similar when limited to periods receiving anti-TNF drug only and did not vary over time. 30-day and 1-year mortality post-MI was not associated with ever-exposure to anti-TNF: adjusted odds ratios (OR) 0.93 (0.29-2.95), OR 0.97 (0.33-2.79) respectively. Conclusions: Subjects with RA ever exposed to anti-TNF experienced a reduced risk of MI over the medium term, further supporting the role of TNF and inflammation in CVD. Disclosure of Interest: None Declared